Romancing the world a biography of Il Divo - Rossi, Allegra (Orion Books, an imprint of the Orion Publishing Group Ltd, 2005)
In Romancing the world, Allegra Rossi reveals where the magic began. She tells of the lives and careers of David Miller, Sebastien Izambard, Urs Buhler and Carlos Marin before they joined the classical supergroup, and how the have worked together to conquer their critics and sing where they are today, on top of the world.